Prevalence, risk factors, and impact of isolated antibody to hepatitis B core antigen and occult hepatitis B virus infection in HIV-1-infected pregnant women - Woottichai Khamduang (2018)
Background. Prevalence and risk factors for isolated antibody to hepatitis B core antigen (anti-HBc) and occult hepatitis B virus (HBV) infection are not well known in human immunodeficiency virus type 1 (HIV-1)-infected pregnant women. It is unclear if women with occult infections are at risk of transmitting HBV to their infants.Methods. HIV-1-infected and HBV surface antigen (HBsAg)-negative pregnant women were tested for antibody to HBsAg (anti-HBs) and anti-HBc using enzyme immunoassay. Women with isolated anti-HBc were assessed for occult HBV infection, defined as HBV DNA levels >15 IU/mL, using the Abbott RealTime HBV DNA assay. Infants born to women with isolated anti-HBc and detectable HBV DNA were tested at 4 months of age for HBV DNA. Logistic regression analysis was used to identify factors associated with isolated anti-HBc and occult HBV infection.Results. Among 1812 HIV-infected pregnant women, 1682 were HBsAg negative. Fourteen percent (95% confidence interval [CI], 12%-15%) of HBsAg-negative women had an isolated anti-HBc that was independently associated with low CD4 count, age >35 years, birth in northern Thailand, and positive anti-hepatitis C virus serology. Occult HBV infection was identified in 24% (95% CI, 18%-30%) of women with isolated anti-HBc, representing 2.6% (95% CI, 1.9%-3.5%) of HIV-1-infected pregnant women, and was inversely associated with HIV RNA levels. None of the women with isolated anti-HBc and occult HBV infection transmitted HBV to their infants.Conclusions. HIV-1-infected pregnant women with isolated anti-HBc and occult HBV infection have very low HBV DNA levels and are thus at very low risk to transmit HBV to their infants. © The Author 2013. Published by Oxford University Press on behalf of the Infectious Diseases Society of America. All rights reserved.